In situ nitrogen-doped helical mesoporous carbonaceous nanotubes for superior-high lithium anodic performance. (April 2018) - Ao, Xiang; Sun, Huayan; Wang, Chundong; Li, Jiangang; Ruan, Yunjun; Li, Baozong; Wu, Qi-Hui; Li, Yi; Jiang, Jianjun; Yang, Yonggang; Mai, Liqiang
Abstract: Carbon with a theoretical lithium storage capacity of 372 mAh g −1  has been widely used in commercial lithium-ion batteries. Increasing the capacity beyond this limit is highly desirable and needed, but challenging. Tailoring the structure and/or introducing heteroatom to carbon lattice may dramatically improve the lithium storage capability. Herein, in situ nitrogen-doped helical mesoporous carbonaceous nanotubes with ultra-high specific surface areas of 1170 m 2  g -1 are designed. Applied as an anode material for LIBs, the as-prepared sample delivers a superior capacity of 1812 mA h g −1 after 150 cycles at a current density of 123 mA g −1, and 1336 mA hg −1 after 300 cycles at 372 mA g −1, suggesting that the unique nanoarchitecture provides plentiful lithium ion storage sites and facilitates the electrolyte and electron transport. The lone pairs of electrons of nitrogen atoms would alter the electronic properties of carbon, facilitating electron donation to Li ions. The strategy of rational design and synthesis of carbon nanostructures offer prospects in developing high-performance energy conversion and storage devices/systems. Graphical abstract: Image 1